REDUCING ACADEMIC PROCRASTINATION THROUGH PROBLEM SOLVING-BASED GROUP GUIDANCE IN SECONDARY EDUCATION - Riski Realfan; Dewi Masyitoh; Ika Romika (EDUCATIONE, 2025)
Academic procrastination remains a persistent barrier to student achievement, self-regulation, and well-being within Indonesia’s secondary education sector, contributing to low academic performance and disengagement. This study aimed to examine the effectiveness of group guidance using problem-solving techniques in reducing academic procrastination among grade XI students at SMK NU 1 Pesanggaran Banyuwangi during the 2024/2025 academic year. Employing a quantitative, pre-experimental design (one-group pretest-posttest), the research targeted six students identified with high academic procrastination from a population of 38, using a validated questionnaire. Over four intervention cycles, group counseling sessions based on problem-solving frameworks were conducted, and changes in procrastination scores were assessed through pre- and posttests. The Wilcoxon signed-rank test revealed a statistically significant reduction in academic procrastination (Z = -2.214, p = 0.027), with all participants improving from high to moderate levels. These results demonstrate the efficacy of structured group guidance rooted in cognitive-behavioral problem-solving in fostering more adaptive academic behaviors and peer-supported accountability. This research contributes to the field by offering empirical evidence for the value of group-based interventions in vocational school contexts—an area often overlooked in Indonesian educational research. The findings support the broader implementation of collaborative, solution-focused counseling practices to promote student discipline, time management, and academic success. It is recommended that future studies employ larger samples, incorporate control groups, and collect qualitative feedback to further enhance the generalizability and understanding of intervention effectiveness.